The Pelvic Girdle Pain deadlock: 2. Topics that, so far, have remained out of focus. (August 2020) - Meijer, O.G.; Barbe, M.F.; Prins, M.R.; Schipholt, I.J. Lutke; Hu, H.; Daffertshofer, A.
Abstract: Introduction: In our preceding paper, we concluded that Pelvic Girdle Pain (PGP) should be taken seriously. Still, we do not know its causes. Literature reviews on treatment fail to reveal a consistent pattern, and there are patients who do not respond well to treatment. We designated the lack of progress in research and in the clinic as 'deadlock', and proposed a 'deconstruction' of PGP, that is to say, taking PGP apart into its relevant dimensions. Purpose: We examine the proposition that PGP may emerge as local inflammation. Inflammation would be a new dimension to be taken into account, between biomechanics and psychology. To explore the consequences of this idea, we present four different topics that, so far, have remained out of focus. One: The importance of microtrauma. Two: Ways to counteract chronification. Three: The importance of sickness behaviour when systemic inflammation turns into neuroinflammation of the brain. And Four: The mainly emotional and cognitive nature of chronic pain, and how aberrant neuroinflammation may render chronic pain intractable. For intractable pain, sleep and stress management are promising treatment options. Implications: The authors hope that the present paper helps to stimulate the flexible creativity that is required to deal with the biological and psychological impact of PGP. Measuring inflammatory mediators in PGP should be a research priority. It should be understood that the boundaries between biology and psychology are becoming blurred. Clinicians must frequently monitor pain, disability, and mood, and be ready to switch treatment whenever the patient does not improve. Highlights: PGP appears to emerge from a microtrauma followed by local inflammation and C fibre nociception. Several measures, including stress management, when relevant, may counteract chronicification. Systemic inflammation induces neuroinflammation, leading to sickness behaviour/demotivation. Chronic pain in PGP goes beyond perception, and implies major emotional and cognitive changes. Intractable pain, with aberrant neuroinflammation, may require sleep and stress management.